Comparison of chemotherapy with or without asparaginase for extranodal nasal NK/T‐cell lymphoma in children and adolescents. Issue 5 (23rd January 2021) - Zhen, Zijun; Huang, Huiqiang; Lin, Tongyu; Li, Zhiming; Zhen, Xi; Xia, Zhongjun; Zhu, Jia; Lu, Suying; Sun, Feifei; Wang, Juan; Huang, Junting; Sun, Xiaofei
Abstract: Purpose: As extranodal natural killer/T‐cell lymphoma (ENKTL) occurs rarely in children and adolescents, standardized therapy is yet to be determined. This study aimed to describe the clinical features and determine the optimal chemotherapy regimen for childhood ENKTL. Methods: The treatment outcomes of radiotherapy combined with asparaginase‐based (P‐GEMOX or P‐GMED) or asparaginase‐absent chemotherapy regimens (CHOP, EPOCH, or NHL‐BFM‐90/95) in patients aged ≤18 years with newly diagnosed ENKTL from December 2006 to December 2018 were compared. Results: Among the 34 patients included in the study, 21 had stage I/II disease. The overall response rates of chemotherapy with or without asparaginase were 85.0% and 78.6%, respectively. With a median follow‐up of 54 months, the 5‐year event‐free survival (EFS) rates of patients with stage I/II and III/IV disease were 66.2 ± 11.3% and 26.0 ± 12.8%, respectively ( P = .027). In stage III/IV patients treated with asparaginase‐based or asparaginase‐absent regimens, the 5‐year EFS rates were 40.0 ± 17.4% and 0%, respectively ( P = .236). The 5‐year EFS rates of stage III/IV patients who received or did not receive hematopoietic stem cell transplant were 66.7 ± 27.2% and 11.1 ± 10.5%, respectively ( P = .054). In addition, chemotherapy‐associated side effects were significantly less in patients treated with asparaginase‐based regimens as compared to asparaginase‐absent regimens in this cohort. Conclusion: P‐GEMOX and P‐GMED regimens are effective and safe for treating childhood ENKTL.